Low shrinkage thermoplastic polyvinyl alcohol film and its preparation method and application
By optimizing the directional stretching process and material ratio, a low-shrinkage, high-strength thermoplastic polyvinyl alcohol film was prepared, solving the problems of high shrinkage and low strength of films in water in the existing technology, and realizing its application as a packaging material in water.
Patent Information
- Application Number
- CN202311511654.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2043-11-14
AI Technical Summary
In the prior art, thermoplastic polyvinyl alcohol films prepared by directional stretching have high shrinkage rate in water, poor dimensional stability, reduced strength, and complex processing technology with high energy consumption, which affects the optical properties of the film.
By employing a directional stretching process, and by selecting appropriate ratios of polyvinyl alcohol, thermoplasticizer, and antioxidant, and controlling the directional stretching temperature, stretching ratio, rate, and annealing time, a low-shrinkage thermoplastic polyvinyl alcohol film is prepared. The film exhibits a shrinkage rate ≤5% in water at 65℃, a tensile strength ≥50MPa in the wet state, and an elongation ≥300%.
A thermoplastic polyvinyl alcohol film with low shrinkage and high strength in water has been developed, which is suitable for packaging materials in water, maintains dimensional stability and strength, reduces energy consumption and improves production stability.
Smart Images

Figure BDA0004547563060000111 
Figure BDA0004547563060000161 
Figure BDA0004547563060000171
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of processing and preparation of high polymer materials, and relates to a low-shrinkage thermoplastic polyvinyl alcohol film, a preparation method and application thereof, which can realize the packaging use of the polyvinyl alcohol film in a water environment. BACKGROUND
[0002] The polyvinyl alcohol molecule side chain has many hydroxyl groups, and the film thereof has excellent water solubility, but limits the application thereof in the hydrophobic field. Directional stretching is a processing technology of melting extrusion of plastic and stretching in a specific direction to prepare a film. The thermoplastic polyvinyl alcohol (TPVA) film prepared by the directional stretching process has the characteristics of high strength and high water-soluble temperature. At present, the thermoplastic agent used in the related researches mostly contains water, which greatly increases the energy consumption and reduces the stability of product production. In addition, the directional stretching process is short in time, the obtained film has high shrinkage in water, poor dimensional stability and obviously reduced strength. Therefore, the development of the TPVA film with excellent optical performance, low shrinkage in water and relatively high strength has become a research and development hotspot at home and abroad.
[0003] Patents CN 106867035A and US2019135997A1 both adopt a solution forming method to prepare a polyvinyl alcohol film. This method has the disadvantages of complex processing technology, high cost, high energy consumption and low production efficiency due to the need of high-temperature drying to remove a large amount of solvent water in the process.
[0004] Patent CN 106189006A uses water as a part of the plasticizer and an inorganic opening agent as an anti-blocking agent, and adopts a biaxial stretching method to prepare a high-temperature water-soluble polyvinyl alcohol film, and the tensile strength is 40 MPa. However, the addition of the opening agent will affect the optical performance of the film. In addition, US patent US2005090589A1 points out that the commonly used organic anti-blocking agent fatty acid amide will also adversely affect the optical performance characteristics of the film.
[0005] Patent CN113105705A uses anhydrous thermoplastic agent and uses a biaxial stretching process to prepare a TPVA film, which significantly improves the performance including the water-soluble temperature and the mechanical properties, but the optical performance is reduced due to the use of the opening agent, and the shrinkage of the film in water is not mentioned. SUMMARY
[0006] In order to overcome the problems in the prior art, the present application provides a low-shrinkage thermoplastic polyvinyl alcohol film, a preparation method and application thereof. The film is directionally stretched by a special process, the film is a high-temperature water-soluble film (water-soluble temperature > 65℃), the shrinkage of the film in 65℃ water is ≤5%, the tensile strength of the film in a wet state is ≥50 MPa, and the elongation of the film is ≥300%.
[0007] One of the objects of the present application is to provide a low shrinkage rate thermoplastic polyvinyl alcohol film, which contains polyvinyl alcohol, a thermoplastic agent and optionally an antioxidant, the film being a high temperature water-soluble film (water-soluble temperature > 65℃), the film having a shrinkage rate of ≤ 5% in water at 65℃.
[0008] In a preferred embodiment, the polyvinyl alcohol is selected from one or more of a mixture of polyvinyl alcohols having a polymerization degree of 1000 to 2500 and an alcoholysis degree of 90 to 99 mol%.
[0009] For example, the polyvinyl alcohol can have a polymerization degree of any point value or any range consisting of any two point values selected from 1000, 1200, 1400, 1600, 1800, 2000, 2200, 2400 or 2500, and an alcoholysis degree of any point value or any range consisting of any two point values selected from 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol% or 99 mol%.
[0010] In a preferred embodiment, the thermoplastic agent is selected from at least one of a small molecule polyol, a polyether polyol and a polyol ester.
[0011] In a further preferred embodiment, the small molecule polyol is selected from at least one of ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, mannitol, xylitol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol and / or the polyether polyol is selected from at least one of polyethylene glycol, polypropylene glycol, polyglycerol, ethylene glycol-propylene glycol copolymer, polypropylene oxide and polytetrahydrofuran and / or the polyol ester is selected from at least one of ethylene glycol ester and glycerol ester.
[0012] In a still further preferred embodiment, the mass ratio of the polyvinyl alcohol to the thermoplastic agent is (60-95):(5-40), preferably (70-95):(5-30).
[0013] For example, the mass ratio of the polyvinyl alcohol to the thermoplastic agent can be any point value or any range consisting of any two point values selected from 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10 or 95:5.
[0014] Preferably, in terms of the total mass of 100% of the polyvinyl alcohol and the thermoplastic agent, the polyvinyl alcohol accounts for 60% to 95%, preferably 70% to 95%, and the thermoplastic agent accounts for 5% to 40%, preferably 5% to 30%.
[0015] In a preferred embodiment, the antioxidant is selected from hindered phenolic antioxidants and / or the bisphosphorus type phosphite antioxidant.
[0016] In a further preferred embodiment, the hindered phenolic antioxidant is selected from at least one of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], oxalyl (diimino-2,1- ethylene) bis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-1,3-propanediylbis(3,5-di-tert- butyl-4-hydroxyphenylpropionamide), 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-thiobis(4-methyl-6-tert- butylphenol), N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexanediamine, 2,2'- methylenebis-(4-methyl-6-tert-butylphenol); and / or, the bisphosphorus type phosphite antioxidant is selected from at least one of pentaerythritol dialkyl diphosphite, pentaerythritol dibutyl diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, tetrakis(2,4-di-tert- butylphenyl-4,4'-biphenyl) bisphosphite.
[0017] In a preferred embodiment, when containing a hindered phenolic antioxidant, the mass ratio of the polyvinyl alcohol and the hindered phenolic antioxidant is (90-99.99):(0.01-10), preferably (99-99.98):(0.02-1), more preferably (99.3-99.95):(0.05-0.7).
[0018] For example, when containing a hindered phenolic antioxidant, the mass ratio of the polyvinyl alcohol and the hindered phenolic antioxidant is any of the point values or any range consisting of any two point values selected from 90:10, 92:8, 94:6, 96:4, 98:2, 99:1, 99.2:0.8, 99.4:0.6, 99.6:0.4, 99.8:0.2, 99.9:0.1, or 99.98:0.02.
[0019] Preferably, the polyvinyl alcohol accounts for 90%-99.99%, preferably 99%-99.98%, more preferably 99.3%-99.95%, and the hindered phenolic antioxidant accounts for 0.01%-10%, preferably 0.02%-1%, more preferably 0.05%-0.7%, based on the total mass of the polyvinyl alcohol and the hindered phenolic antioxidant being 100%.
[0020] In a preferred embodiment, when containing bisphosphorus type phosphite antioxidant, the mass ratio of the thermoplastic agent to the bisphosphorus type phosphite antioxidant is (90-99.99):(0.01-10), preferably (99-99.98):(0.02-1), more preferably (99.5-99.9):(0.1-0.5).
[0021] For example, when containing bisphosphorus type phosphite antioxidant, the mass ratio of the thermoplastic agent to the bisphosphorus type phosphite antioxidant is any of the point values or any range consisting of any two point values selected from the group consisting of 90:10, 92:8, 94:6, 96:4, 98:2, 99:1, 99.2:0.8, 99.4:0.6, 99.6:0.4, 99.8:0.2, 99.9:0.1 and 99.98:0.02.
[0022] Preferably, when containing bisphosphorus type phosphite antioxidant, the thermoplastic agent accounts for 90%-99.99%, preferably 99%-99.98%, more preferably 99.5%-99.9%, and the bisphosphorus type phosphite antioxidant accounts for 0.01%-10%, preferably 0.02%-1%, more preferably 0.1%-0.5%, based on the total mass of the thermoplastic agent and bisphosphorus type phosphite antioxidant.
[0023] In a preferred embodiment, the ratio of the total mass of the polyvinyl alcohol and hindered phenolic antioxidant to the total mass of the thermoplastic agent and bisphosphorus type phosphite antioxidant is (60-95):(5-40), preferably (65-90):(10-35), for example any of the point values or any range consisting of any two point values selected from the group consisting of 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10 and 95:5.
[0024] Preferably, the total mass of the polyvinyl alcohol and hindered phenolic antioxidant accounts for 60%-95%, preferably 65%-90%, and the total mass of the thermoplastic agent and bisphosphorus type phosphite antioxidant accounts for 5%-40%, preferably 10%-35%, based on the total mass of the polyvinyl alcohol, hindered phenolic antioxidant, thermoplastic agent and bisphosphorus type phosphite antioxidant.
[0025] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film has a shrinkage in water at 65°C of ≤5%.
[0026] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film has a tensile strength in wet state of ≥50 MPa.
[0027] The low-shrinkage thermoplastic polyvinyl alcohol film has a transverse tensile strength and a longitudinal tensile strength each independently ≥ 50 MPa in a wet state.
[0028] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film has a transverse breaking elongation and a longitudinal breaking elongation each independently ≥ 300%.
[0029] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film has an average thickness of 5-50 μm, preferably 10-30 μm, for example any of 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm or any range defined by any two of them.
[0030] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film is prepared by a directional stretching process.
[0031] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film is prepared by a directional stretching process.
[0032] In a further preferred embodiment, the conditions of the directional stretching include: the preheating and stretching temperature each independently is 200-250 °C (200 °C can be preferably excluded), preferably 200-230 °C; and / or, the stretching ratio (the product of the longitudinal stretching ratio and the transverse stretching ratio) is 9-64, preferably 16-49; and / or, the stretching rate is 10-100% / sec (10% / sec can be preferably excluded); and / or, the annealing temperature is 200-280 °C, preferably 200-240 °C; and / or, the annealing time is 2-100 s, preferably 5-70 s.
[0033] For example, the conditions of the directional stretching include: each of the preheating and stretching temperatures is independently any point value or any range consisting of any two point values selected from the group consisting of 200℃, 210℃, 220℃, 230℃, 240℃ or 250℃; and / or, the stretching multiple (the product of the longitudinal stretching multiple and the transverse stretching multiple) is any point value or any range consisting of any two point values selected from the group consisting of 9, 16, 25, 36, 49 or 64; and / or, the stretching rate is any point value or any range consisting of any two point values selected from the group consisting of 10% / sec, 20% / sec, 30% / sec, 40% / sec, 50% / sec, 60% / sec, 70% / sec, 80% / sec, 90% / sec or 100% / sec; and / or, the annealing temperature is any point value or any range consisting of any two point values selected from the group consisting of 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃ or 280℃; and / or, the annealing time is any point value or any range consisting of any two point values selected from the group consisting of 2s, 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s or 100s.
[0034] In a further preferred embodiment, the conditions of the directional stretching include: each of the preheating and stretching temperatures is independently 200-220℃, the stretching multiple (the product of the longitudinal stretching multiple and the transverse stretching multiple) is preferably 16-36, the stretching rate is 25-90% / sec, the annealing temperature is 200-230℃, and the annealing time is 5-40s, so as to obtain a thermoplastic polyvinyl alcohol film with an average thickness of preferably 10-30μm.
[0035] In the above directional stretching process (especially at the preheating and stretching temperatures, the annealing temperature and the annealing time), the inventors have found that the obtained film not only has a high water-soluble temperature, but also has a low shrinkage in water and good mechanical properties.
[0036] In the present application, the polyhydroxy structure of the polyvinyl alcohol makes the film product easy to dissolve in water or stick after long storage, although it has excellent water-solubility, it limits its application in the hydrophobic field. Therefore, the polyvinyl alcohol products on the market are generally used in the water-soluble packaging field, i.e. the film dissolves in water and releases the contents. However, if the polyvinyl alcohol is to be applied to daily packaging scenarios, the physical form and various properties of the film when it comes into contact with water or is placed in water must be considered, such as whether the film can maintain dimensional stability and retain the necessary strength as a wet garbage bag or express packaging. The low-shrinkage thermoplastic polyvinyl alcohol film of the present application is prepared by directional stretching process, which is a high-temperature water-soluble film (water-soluble temperature > 65℃), the shrinkage of the film in 65℃ water is ≤5%, the tensile strength under wet state is ≥50MPa, and the elongation rate is ≥300%.
[0037] The second object of the present application is to provide a method for preparing the low-shrinkage thermoplastic polyvinyl alcohol film according to the first object of the present application, comprising: (1) extruding and granulating raw materials including the polyvinyl alcohol, the thermoplastic agent, and optionally the antioxidant; (2) melt extruding into a sheet; and (3) orienting and stretching the sheet to obtain the low-shrinkage thermoplastic polyvinyl alcohol film.
[0038] In a preferred embodiment, in step (1), the raw materials including the polyvinyl alcohol, the thermoplastic agent, and optionally the antioxidant are added to a screw extruder I (e.g., a twin-screw extruder) to obtain a thermoplastic polyvinyl alcohol resin by melting, kneading, and extruding.
[0039] In a further preferred embodiment, the conditions of the screw extruder I include an extrusion temperature of 140-240°C, preferably 180-220°C; and / or a screw rotation speed of 50-500 rpm, preferably 150-350 rpm.
[0040] For example, the conditions of the screw extruder I include an extrusion temperature of any point value or any range consisting of any two point values selected from 140°C, 160°C, 180°C, 200°C, 220°C, and 240°C; and / or a screw rotation speed of any point value or any range consisting of any two point values selected from 50 rpm, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, and 500 rpm.
[0041] In the above technical solution, the method for preparing the low-shrinkage thermoplastic polyvinyl alcohol film is a twin-screw continuous melt blending extrusion method, preferably the dry-treated polyvinyl alcohol, the thermoplastic agent, and the antioxidant are blended according to the desired proportions and then added to a twin-screw extruder to melt, knead, extrude, and granulate to obtain the thermoplastic polyvinyl alcohol resin; more preferably, the dry-treated polyvinyl alcohol, the thermoplastic agent, and the antioxidant are directly added to a twin-screw extruder to melt, knead, extrude, and granulate to obtain the thermoplastic polyvinyl alcohol resin.
[0042] The thermoplastic polyvinyl alcohol (TPVA) is a high-melt-strength and high-flowability polyvinyl alcohol obtained by thermoplastic modification of polyvinyl alcohol to improve the processing difficulty and poor melt flowability of polyvinyl alcohol due to intramolecular and intermolecular forces, and has a widened processing temperature window and significantly improved thermoplastic processing performance. The thermoplastic polyvinyl alcohol of the present application can be processed by a twin-screw melt blending extrusion technology, and the above-mentioned polyvinyl alcohol, thermoplastic agent, and optional antioxidant are blended according to the proportions and then introduced or directly introduced for melt blending extrusion.
[0043] In a preferred embodiment, in step (2), the melt extrusion is performed in a second screw extruder (e.g., a single screw extruder), and a film-forming die (preferably a cast film die or a blown film die) is provided at the discharge end of the second screw extruder to obtain the thermoplastic polyvinyl alcohol sheet.
[0044] In a further preferred embodiment, the conditions of the second screw extruder include a melt extrusion temperature of 140-240°C, preferably 180-220°C; and / or the temperature of the film-forming die is 150-250°C, preferably 190-230°C.
[0045] For example, the conditions of the second screw extruder include a melt extrusion temperature of any point value or any range consisting of any two point values selected from 140°C, 160°C, 180°C, 200°C, 220°C, or 240°C; and / or the temperature of the film-forming die is any point value or any range consisting of any two point values selected from 150°C, 160°C, 180°C, 200°C, 220°C, 240°C, or 250°C.
[0046] In a still further preferred embodiment, the average thickness of the thermoplastic polyvinyl alcohol sheet is 300-600 μm, preferably 350-550 μm, for example any point value or any range consisting of any two point values selected from 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, or 600 μm.
[0047] In the above technical solution, the thermoplastic polyvinyl alcohol resin is melt extruded from a single screw extruder and then discharged through a cast film die or a blown film die to obtain a thermoplastic polyvinyl alcohol sheet with an average thickness of 300-600 μm, preferably 350-550 μm.
[0048] In a preferred embodiment, in step (3), the conditions of the orientational stretching include that the preheating and stretching temperatures are each independently 200-250°C (200°C can be preferably excluded), preferably 200-230°C; and / or the stretching multiple (the product of the longitudinal stretching multiple and the transverse stretching multiple) is 9-64, preferably 16-49; and / or the stretching rate is 10-100% / sec (10% / sec can be preferably excluded); and / or the annealing temperature is 200-280°C, preferably 200-240°C; and / or the annealing time is 2-100 s, preferably 5-70 s.
[0049] For example, in step (3), the conditions of the directional stretching include: each of the preheating and stretching temperatures is independently any point value or any range consisting of any two point values selected from the group consisting of 200°C, 210°C, 220°C, 230°C, 240°C or 250°C; and / or, the stretching multiple (the product of the longitudinal stretching multiple and the transverse stretching multiple) is any point value or any range consisting of any two point values selected from the group consisting of 9, 10, 15, 16, 20, 25, 30, 36, 40, 45, 49, 50, 55, 60 or 64; and / or, the stretching rate is any point value or any range consisting of any two point values selected from the group consisting of 10% / sec, 20% / sec, 30% / sec, 40% / sec, 50% / sec, 60% / sec, 70% / sec, 80% / sec, 90% / sec or 100% / sec; and / or, the annealing temperature is any point value or any range consisting of any two point values selected from the group consisting of 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C or 280°C; and / or, the annealing time is any point value or any range consisting of any two point values selected from the group consisting of 2s, 5s, 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s or 100s.
[0050] In a further preferred embodiment, in step (3), the conditions of the directional stretching include: each of the preheating and stretching temperatures is independently 200-220°C; and / or, the stretching multiple (the product of the longitudinal stretching multiple and the transverse stretching multiple) is 16-36; and / or, the stretching rate is 25-90% / sec; and / or, the annealing temperature is 200-230°C; and / or, the annealing time is 5-40s; to obtain a thermoplastic polyvinyl alcohol film having an average thickness of 5-50μm, preferably 10-30μm.
[0051] The inventors have found through a large number of experimental studies that:
[0052] (1) The preheating and stretching temperatures, the stretching rate, the annealing temperature and the annealing time are key parameters of the directional stretching process of TPVA. With the increase of the values, the shrinkage of the film decreases, and when the stretching multiple reaches a certain value, it no longer affects the shrinkage of the film. This may be because with the increase of the preheating and stretching temperatures, the molecular chain movement is easier, and at the same temperature, the increase of the stretching rate further speeds up the molecular chain movement, and the higher the annealing temperature or the longer the annealing time, the more perfect the molecular chain movement, thereby changing the crystallinity and structural regularity, and thus affecting the water-soluble temperature and the shrinkage.
[0053] (2) With the increase of the temperature of preheating and stretching section or the annealing temperature, the tensile strength and elongation of the film increase simultaneously, because the structure regularity after stretching is better with the increase of the stretching temperature, the strength of the film increases in high temperature water (for example, 60℃ water) and the elongation also increases because the molecular chain is more relaxed; and the crystallization is more perfect with the increase of the annealing temperature, so the tensile strength of the film increases.
[0054] In a further preferred embodiment, in the orientated stretching of step (3), the transverse stretching ratio is 3-8, preferably 4-7; and the longitudinal stretching ratio is 3-8, preferably 4-7.
[0055] For example, in the orientated stretching of step (3), the transverse stretching ratio is any point value or any range consisting of any two point values selected from 3, 4, 5, 6, 7 or 8; and the longitudinal stretching ratio is any point value or any range consisting of any two point values selected from 3, 4, 5, 6, 7 or 8.
[0056] In the present application, the preparation method comprises: adding raw materials including polyvinyl alcohol, thermoplastic agent and antioxidant into a double-screw extruder, and obtaining a thermoplastic polyvinyl alcohol resin through melting, kneading and extruding; and obtaining the low-shrinkage high-strength thermoplastic polyvinyl alcohol film through melting extruding the thermoplastic polyvinyl alcohol resin into a sheet through a single-screw extruder and then orientated stretching the sheet.
[0057] The continuous double-screw extrusion equipment suitable for the present application includes double-screw extruders with different designs, such as the ZSK Mcc18 co-rotating parallel double-screw extruder produced by Coperion, Germany, etc. The biaxial stretching equipment suitable for the present application includes biaxial stretching machines with different designs, such as the Karo IV biaxial stretching experimental machine produced by Brückner, Germany, etc.
[0058] The third object of the present application is to provide a low-shrinkage thermoplastic polyvinyl alcohol film obtained by the preparation method of the second object of the present application.
[0059] The low-shrinkage thermoplastic polyvinyl alcohol film is a high-temperature water-soluble film (water-soluble temperature > 65℃), the shrinkage of the film in 65℃ water is ≤5%, the tensile strength in wet state is ≥50MPa, and the elongation is ≥300%, achieving good technical effects. The polyvinyl alcohol film has low shrinkage and high strength in water.
[0060] The fourth object of the present application is to provide the application of the low-shrinkage thermoplastic polyvinyl alcohol film of the first object of the present application or the low-shrinkage thermoplastic polyvinyl alcohol film obtained by the preparation method of the second object of the present application in packaging materials.
[0061] In a preferred embodiment, the low-shrinkage thermoplastic polyvinyl alcohol film is used in wet garbage bags and express delivery bags.
[0062] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values; these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In the following, various technical solutions can, in principle, be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.
[0063] Compared with the prior art, the present invention has the following beneficial effects: the low shrinkage thermoplastic polyvinyl alcohol film is a high-temperature water-soluble film (water-soluble temperature > 65℃), the film has a shrinkage rate ≤ 5% in water at 65℃, a tensile strength ≥ 50MPa in wet state, and an elongation ≥ 300%, thus achieving better technical results. Detailed Implementation
[0064] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0065] It should also be noted that the various specific technical features described in the following embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the various possible combinations will not be described separately in this invention.
[0066] Furthermore, various embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention. The resulting technical solutions are part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0067] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0068] The performance of this invention was determined according to the following method:
[0069] Thin film thickness testing: A handheld spiral thickness gauge manufactured by Mahr Measurement Instruments GmbH, Germany, was used for testing. Five dispersed locations in the middle part of the thin film were selected for testing, and the average value was taken.
[0070] Shrinkage test of film: square film with length and width of 6 cm and 6 cm was cut, and the transverse and longitudinal directions were marked. The sample was immersed in 60°C pure water (water temperature was constant) for 30 min for sufficient water absorption, then the sample was taken out, and the length and width of the film at this time were measured, recorded as L1 and L2 (unit: cm), respectively. The shrinkage (S) of the film was calculated according to the following formula:
[0071]
[0072] The measurement was repeated three times and the average value was taken.
[0073] Tensile property test of film in wet state: the film sample was immersed in 60°C pure water (water temperature was constant) for 30 min, then the sample was taken out, and Type 5 sample strip in ISO527-3 standard was cut along the longitudinal tensile direction (parallel to the casting direction, MD direction) and the transverse tensile direction (perpendicular to the casting direction, TD direction) of the film respectively. The test was carried out according to ISO 527-3 standard using Instron 3344 material testing machine, and the processing software was Bluehill 2.31 version. During the test, the initial clamp distance was 75 mm, the test tensile rate was 100 mm / min, each sample was tested at least 5 times, and the average value was taken. During the test, the film was always in wet state.
[0074]
Comparative Example 1
[0075] The polyvinyl alcohol used had a polymerization degree of 1300 and an alcoholysis degree of 98%, and was prepared by using a PolyLab HAAKE TMThe Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16mm, L / D = 40) performs thermoplasticization, extrusion, and granulation. The extruder has 11 sections from the feed inlet to the die, numbered 1-11. Section 1 is only for feeding and cannot be heated. The powder feeder attached to the extruder, after calibration, is used to feed polyvinyl alcohol and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] (mass ratio 99.9:0.1) into the twin screw at a feed rate of 835 g / hr. Thermoplasticizer (by mass fraction, a mixture containing 84% glycerol, 7% pentaerythritol, and 9% tripropylene glycol) and pentaerythritol dialkyl diphosphite (mass ratio 99.8:0.2) are added to the extruder through the feed inlet at a feed rate of 165 g / hr. The temperatures of extruder sections 2-11 are 180℃, 190℃, 200℃, 200℃, 200℃, 200℃, 200℃, 200℃, and 190℃, respectively, with the screw speed set at 300 rpm. This extruder is equipped with a 3mm diameter circular die. After extrusion and air cooling, the sample is chopped into approximately 3mm thermoplastic polyvinyl alcohol (TPVA) particles using a pelletizer. The particles are collected and packaged for later use.
[0076] The aforementioned TPVA particles were manufactured in HAAKE at Thermo Fisher Scientific in the United States. TM Sheets are produced by extrusion casting on a Rheomex OS single-screw extruder with a screw diameter of 19 mm and an aspect ratio of 25. The extruder is equipped with a 3:1 standard metering screw and is manufactured by PolyLab HAAKE. TM OS torque rheometer platform control. The extruder has three heating sections with temperatures of 190℃, 200℃, and 200℃ from the inlet to the outlet, respectively. The TPVA melt is extruded through a flat die (die temperature is 200℃), pulled by a series of rollers at the front end, cooled, and then wound up. The average thickness of the TPVA sheet is 375μm.
[0077] The aforementioned thin films were subjected to directional stretching on a Karo IV biaxial stretching testing machine manufactured by Brückner GmbH, Germany. This equipment has three modular sections; in this invention, only the first two sections are used. The first section is the preheating and stretching section, with a preheating and stretching temperature of 170°C, a stretching ratio of 25 (5 in the transverse direction and 5 in the longitudinal direction), and a stretching rate of 30% / sec. The second section is the annealing section, with an annealing temperature of 200°C and an annealing time of 15 s. The average thickness of the monolayer TPVA film obtained by directional stretching is 15 μm.
[0078] [Comparative Example 2]
[0079] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 180°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 200°C, and the annealing time is 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching is 15 μm.
[0080] [Comparative Example 3]
[0081] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 190°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 200°C, and the annealing time is 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching is 15 μm.
[0082] [Comparative Example 4]
[0083] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 200°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 130°C, and the annealing time is 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching is 15 μm.
[0084] [Comparative Example 5]
[0085] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 200°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 160°C, and the annealing time is 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching is 15 μm.
[0086] [Comparative Example 6]
[0087] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 200°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 190°C, and the annealing time is 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching is 15 μm.
[0088] [Comparative Example 7]
[0089] The method according to Comparative Example 1, except that the first stage was a preheating and stretching stage, the preheating and stretching temperature was 200°C, the stretching ratio was 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate was 10% / sec; the second stage was an annealing stage, the annealing temperature was 200°C, and the annealing time was 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching was 15 μm.
[0090] [Example 1]
[0091] The method according to Comparative Example 1, except that the first stage was a preheating and stretching stage, the preheating and stretching temperature was 200°C, the stretching ratio was 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate was 30% / sec; the second stage was an annealing stage, the annealing temperature was 200°C, and the annealing time was 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching was 15 μm.
[0092] [Example 2]
[0093] The method according to Comparative Example 1, except that the average thickness of the TPVA sheet was 454 μm. The first stage was a preheating and stretching stage, the preheating and stretching temperature was 200°C, the stretching ratio was 30.25 (5.5 in the transverse direction and 5.5 in the longitudinal direction), and the stretching rate was 30% / sec; the second stage was an annealing stage, the annealing temperature was 200°C, and the annealing time was 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching was 15 μm.
[0094] [Example 3]
[0095] The method according to Comparative Example 1, except that the average thickness of the TPVA sheet was 540 μm. The first stage was a preheating and stretching stage, the preheating and stretching temperature was 200°C, the stretching ratio was 36 (6 in the transverse direction and 6 in the longitudinal direction), and the stretching rate was 30% / sec; the second stage was an annealing stage, the annealing temperature was 200°C, and the annealing time was 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching was 15 μm.
[0096] [Example 4]
[0097] The method according to Comparative Example 1, except that the first stage was a preheating and stretching stage, the preheating and stretching temperature was 200°C, the stretching ratio was 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate was 50% / sec; the second stage was an annealing stage, the annealing temperature was 200°C, and the annealing time was 15 seconds. The average thickness of the single-layer TPVA film obtained by the directional stretching was 15 μm.
[0098] [Example 5]
[0099] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 200°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 70% / sec; the second stage is an annealing stage, the annealing temperature is 200°C, and the annealing time is 15s. The average thickness of the single-layer TPVA film obtained by directional stretching is 15μm.
[0100] [Example 6]
[0101] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 200°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 200°C, and the annealing time is 5s. The average thickness of the single-layer TPVA film obtained by directional stretching is 15μm.
[0102] [Example 7]
[0103] The method according to Comparative Example 1, except that the first stage is a preheating and stretching stage, the preheating and stretching temperature is 200°C, the stretching ratio is 25 (5 in the transverse direction and 5 in the longitudinal direction), and the stretching rate is 30% / sec; the second stage is an annealing stage, the annealing temperature is 200°C, and the annealing time is 25s. The average thickness of the single-layer TPVA film obtained by directional stretching is 15μm.
[0104] [Example 8]
[0105] The method according to Example 1, except that after calibration, polyvinyl alcohol raw material and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] (mass ratio of 99.8:0.2) are fed into the twin screw at a feeding speed of 835g / hr. Thermoplastic agent (thermoplastic agent is a mixture containing 84% glycerol, 7% pentaerythritol, and 9% tripropylene glycol by mass fraction) and pentaerythritol dialkyl diphosphite (mass ratio of 99.6:0.4) are added to the extruder through the feeding port at a feeding rate of 165g / hr.
[0106] [Example 9]
[0107] The method according to Example 1, except that after calibration, polyvinyl alcohol raw material and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] (mass ratio 99.6:0.4) were fed into the twin-screw extruder at a feeding speed of 835 g / hr. Thermoplastics (thermoplastics were a mixture containing 84% glycerol, 7% pentaerythritol, and 9% tripropylene glycol by mass fraction) and pentaerythritol dialkyl diphosphite (mass ratio 99.2:0.8) were added into the extruder through the feeding port at a feeding speed of 165 g / hr.
[0108] Example 10
[0109] The method according to Example 1, except that the temperatures of the 2-11 sections of the extruder were 190°C, 195°C, 205°C, 205°C, 205°C, 205°C, 205°C, 205°C, 205°C, and 195°C, respectively, and the screw rotation speed was set at 250 rpm.
[0110] Example 11
[0111] The method according to Example 1, except that the temperatures of the 2-11 sections of the extruder were 170°C, 180°C, 190°C, 190°C, 190°C, 190°C, 190°C, 190°C, 190°C, and 180°C, respectively, and the screw rotation speed was set at 350 rpm.
[0112] Example 12
[0113] The method according to Example 1, except that the temperatures of the single-screw extruder from the feeding port to the outlet were 170°C, 180°C, and 180°C, respectively, and the TPVA melt was extruded through a flat die (die temperature 180°C).
[0114] Example 13
[0115] The method according to Example 1, except that the temperatures of the single-screw extruder from the feeding port to the outlet were 200°C, 210°C, and 210°C, respectively, and the TPVA melt was extruded through a flat die (die temperature 210°C).
[0116] Test Example 1
[0117] The water-solubility and shrinkage of 20 kinds of TPVA oriented stretch films including Comparative Examples 1-7 and Examples 1-13 were tested according to the above method, and the effects of different processing techniques on the water-solubility temperature and shrinkage of the films were mainly investigated, and the results are shown in Table 1.
[0118] Table 1 Water-solubility temperature and shrinkage of film samples
[0119]
[0120]
[0121] From Table 1, the shrinkage of the TPVA oriented stretch film of the present application in 65℃ water is ≤5%.
[0122]
Test Example 2
[0123] The 20 kinds of TPVA oriented stretch films including Comparative Examples 1-7 and Examples 1-13 are tested for the tensile property in wet state according to the above description, mainly to investigate the influence of different processing technology on the tensile property of the film in wet state, and the results are shown in Table 2.
[0124] Table 2 Tensile property (MD) of each sample film
[0125]
[0126]
[0127] Table 3 Tensile property (TD) of each sample film
[0128]
[0129] From Table 2 and Table 3, the breaking tensile strength of the TPVA oriented stretch film of the present application in wet state is ≥50MPa, and the elongation is ≥300%.
[0130] From Comparative Examples 1-6, the films of Comparative Examples 1-6 all show soft and weak characteristics in 60℃ water.
[0131] From Comparative Example 7 and Examples 1, 4 and 5, with the increase of the stretching rate, the tensile strength of the film increases, and the elongation increases first and then decreases, because when the stretching rate is ≤10% / sec, the crystallization of the film is not perfect, and the strength and elongation in wet state are low, and with the increase of the rate, the stretching rate increases, the crystallization is easier and the perfection is better, which shows that the tensile strength of the film increases, but the elongation decreases.
[0132] From Comparative Examples 1-3, the tensile strength of the film increases with the increase of the stretching multiple, and the elongation decreases. From Examples 1, 6 and 7, the same technical effect is obtained with the increase of the annealing time.
[0133] From Comparative Examples 1 and 8-13, it is known that changing the ratio of phosphite and hindered phenolic antioxidant and the processing parameters of the granules and flakes in a certain range has no effect on the shrinkage and mechanical properties of the film in wet state.
[0134] The present application is described in detail above with reference to specific embodiments and exemplary examples, but these are not to be understood as limiting the present application. It is understood by a person skilled in the art that various equivalent substitutions, modifications or improvements can be made to the technical solutions of the present application and the embodiments thereof without departing from the spirit and scope of the present application, and these all fall within the scope of the present application. The scope of protection of the present application is defined by the appended claims.
Claims
1. A low-shrinkage thermoplastic polyvinyl alcohol film, comprising polyvinyl alcohol, a thermoplasticizer, and optionally an antioxidant, wherein the film is a high-temperature water-soluble film, and the film has a shrinkage rate ≤5% in water at 65°C; wherein the polyvinyl alcohol is selected from one or more polyvinyl alcohols with a degree of polymerization of 1000-2500 and a degree of alcoholysis of 90-99 mol%; wherein the thermoplasticizer is selected from at least one of small molecule polyols, polyether polyols, and polyol esters; the method for preparing the low-shrinkage thermoplastic polyvinyl alcohol film includes: (1) Extruding and granulating the raw material comprising the polyvinyl alcohol, the thermoplasticizer, and optionally the antioxidant; (2) Melt extrusion into thin sheets; (3) The sheet is oriented and stretched to obtain the low-shrinkage thermoplastic polyvinyl alcohol film; In step (3), the conditions for directional stretching include: preheating and stretching temperatures are each independently 200~250ºC, stretching rate is 30~100% / sec, and annealing temperature is 200~240ºC.
2. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 1, characterized in that, The small molecule polyol is selected from at least one of ethylene glycol, propylene glycol, glycerol, pentaerythritol, sorbitol, mannitol, xylitol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, and tetrapropylene glycol; and / or, the polyether polyol is selected from at least one of polyethylene glycol, polypropylene glycol, polyglycerol, ethylene glycol-propylene glycol copolymer, polypropylene oxide, and polytetrahydrofuran; and / or, the polyol ester is selected from at least one of ethylene glycol esters and glycerol esters.
3. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol to thermoplasticizer is (60~95):(5~40).
4. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol to thermoplasticizer is (70~95):(5~30).
5. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 1, characterized in that, The antioxidant is selected from hindered phenolic antioxidants and / or diphosphite antioxidants.
6. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 5, characterized in that, The hindered phenolic antioxidant is selected from triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], (3,5-di-tert-butyl-4-hydroxyphenyl)propionate oxaloyl(diimino-2,1-ethylidene) ester, N,N'-1,3-propylidene di[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 2,2'- At least one of thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-thiobis(4-methyl-6-tert-butylphenol), N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexamethylenediamine, and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol); and / or, the bisphosphite antioxidant is selected from at least one of pentaerythritol dialkyl diphosphite, pentaerythritol diphosphite bisoctadecyl, bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, and tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl) bisphosphite.
7. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 5, characterized in that, When the product contains hindered phenolic antioxidants, the mass ratio of polyvinyl alcohol to hindered phenolic antioxidants is (90~99.99):(0.01~10); when the product contains diphosphite antioxidants, the mass ratio of thermoplasticizer to diphosphite antioxidants is (90~99.99):(0.01~10).
8. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 5, characterized in that, When the product contains hindered phenolic antioxidants, the mass ratio of polyvinyl alcohol to hindered phenolic antioxidants is (99~99.98):(0.02~1); when the product contains diphosphite antioxidants, the mass ratio of thermoplasticizer to diphosphite antioxidants is (99~99.98):(0.02~1).
9. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 5, characterized in that, When the product contains hindered phenolic antioxidants, the mass ratio of polyvinyl alcohol to hindered phenolic antioxidants is (99.3~99.95):(0.05~0.7); when the product contains diphosphite antioxidants, the mass ratio of thermoplasticizer to diphosphite antioxidants is (99.5~99.9):(0.1~0.5).
10. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 1, characterized in that, The ratio of the total mass of the polyvinyl alcohol and hindered phenolic antioxidants to the total mass of the thermoplasticizer and diphosphite antioxidants is (60~95):(5~40).
11. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 1, characterized in that, The ratio of the total mass of the polyvinyl alcohol and hindered phenolic antioxidants to the total mass of the thermoplasticizer and diphosphite antioxidants is (65~90): (10~35).
12. The low-shrinkage thermoplastic polyvinyl alcohol film according to any one of claims 1 to 11, characterized in that, The low-shrinkage thermoplastic polyvinyl alcohol film has a tensile strength ≥50 MPa in the wet state; and / or, The low-shrinkage thermoplastic polyvinyl alcohol film has a transverse elongation at break and a longitudinal elongation at break that are each independently ≥300%; and / or, The average thickness of the low-shrinkage thermoplastic polyvinyl alcohol film is 5~50μm.
13. The low-shrinkage thermoplastic polyvinyl alcohol film according to claim 12, characterized in that, The average thickness of the low-shrinkage thermoplastic polyvinyl alcohol film is 10~30μm.
14. A method for preparing a low-shrinkage thermoplastic polyvinyl alcohol film, used to prepare the low-shrinkage thermoplastic polyvinyl alcohol film according to any one of claims 1 to 13, the preparation method comprising: (1) Extruding and granulating the raw material comprising the polyvinyl alcohol, the thermoplasticizer, and optionally the antioxidant; (2) Melt extrusion into thin sheets; (3) The sheet is oriented and stretched to obtain the low-shrinkage thermoplastic polyvinyl alcohol film; the preheating and stretching temperatures are 200~250ºC, the stretching rate is 30~100% / sec, and the annealing temperature is 200~240ºC.
15. The preparation method according to claim 14, characterized in that, In step (1), raw materials including polyvinyl alcohol, thermoplasticizer, and optional antioxidant are added to screw extruder 1, and thermoplastic polyvinyl alcohol resin is obtained by melting, kneading and extrusion.
16. The preparation method according to claim 15, characterized in that, The conditions for the screw extruder include: an extrusion temperature of 140~240ºC; and / or a screw speed of 50~500rpm.
17. The preparation method according to claim 15, characterized in that, The conditions of the screw extruder include: an extrusion temperature of 180~220ºC; and / or a screw speed of 150~350rpm.
18. The preparation method according to claim 14, characterized in that, In step (2), the melt extrusion is carried out in the screw extruder 2, and a film-forming die head is provided at the discharge end of the screw extruder 2 to obtain thermoplastic polyvinyl alcohol sheets.
19. The preparation method according to claim 18, characterized in that, The conditions for the second screw extruder include: a melt extrusion temperature of 140~240ºC; and / or, a film-forming die temperature of 150~250ºC.
20. The preparation method according to claim 18, characterized in that, The conditions for the second screw extruder include: a melt extrusion temperature of 180~220ºC; and / or, a film-forming die temperature of 190~230ºC.
21. The preparation method according to any one of claims 14 to 20, characterized in that, In step (3), the conditions for directional stretching include: The preheating and stretching temperatures are each independently 200~230ºC; and / or, The stretch ratio is 9 to 64; and / or, Annealing time is 2~100s.
22. The preparation method according to claim 21, characterized in that, In step (3), the conditions for directional stretching include: The stretch ratio is 16~49; and / or, Annealing time is 5~70 s.
23. A low-shrinkage thermoplastic polyvinyl alcohol film obtained by the preparation method according to any one of claims 14 to 22.
24. The use of the low-shrinkage thermoplastic polyvinyl alcohol film according to any one of claims 1 to 13 or the low-shrinkage thermoplastic polyvinyl alcohol film obtained by the preparation method according to any one of claims 14 to 22 in packaging materials.
25. The application according to claim 24, characterized in that, Application of the low-shrinkage thermoplastic polyvinyl alcohol film in wet garbage bags and express delivery bags.
Citation Information
Patent Citations
Biaxial orienting drawing formed polyvinyl alcohol membrane and production method thereof
CN106189006A
Modified polyvinyl alcohol packaging film and preparation method thereof
CN106867035A
Thermoplastic polyvinyl alcohol composition film with high-temperature water solubility as well as preparation method and application of thermoplastic polyvinyl alcohol composition film
CN113105705A
Polyvinyl butyral sheet having antiblocking characteristics
US20050090589A1
Water soluble film, packets employing the film, and methods of making and using same
US20190135997A1